Map-Based Web Tools Supporting Climate Change Adaptation. Issue 1 (2nd January 2016) - Neset, Tina-Simone; Opach, Tomasz; Lion, Peter; Lilja, Anna; Johansson, Jimmy
Abstract : This article discusses the state of the art in geovisualization supporting climate change adaptation. We reviewed twenty selected map-based Web tools, classified by their content and functionality, and assessed them by visual representations, interactive functions, information type, target audience, and how vulnerability and adaptation to climate change are addressed. Our study concludes that the tools (1) can be classified as data viewers with basic functionality and data explorers offering more sophisticated interactive functions; (2) mostly feature moderate or high richness of data content; and (3) predominantly target expert users.